2008
DOI: 10.1002/jnr.21849
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and role ofHelixcontactin‐related proteins in culturedHelix pomatianeurons

Abstract: We report on the structural and functional properties of the Helix contactin-related proteins (HCRPs), a family of closely related glycoproteins previously identified in the nervous system of the land snail Helix pomatia through antibodies against the mouse F3/contactin glycoprotein. We focus on HCRP1 and HCRP2, soluble FNIII domains-containing proteins of 90 and 45 kD bearing consensus motifs for both N- and O-glycosylation. Using the anti-HCRPs serum, we find secreted HCRPs in Helix nervous tissue isotonic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Importantly, cells in culture have been validated as accurately reflecting in vivo neuronal function by cell ablation-complementation (Syed et al 1992), and by anti-sense blocking (Milanese et al 2009). In other studies, in vitro vs. in vivo cellular responses to specific chemical agents were compared (Fiumara et al 2005) and found to be similar.…”
Section: Molluscan Primary Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, cells in culture have been validated as accurately reflecting in vivo neuronal function by cell ablation-complementation (Syed et al 1992), and by anti-sense blocking (Milanese et al 2009). In other studies, in vitro vs. in vivo cellular responses to specific chemical agents were compared (Fiumara et al 2005) and found to be similar.…”
Section: Molluscan Primary Cell Culturesmentioning
confidence: 99%
“…The following are examples of the main types of research conducted using cultured neuronal cells. (1) identification and functional characterization of neurotrophic factors regulating neurite outgrowth and regeneration (Spence et al 1998; Goldberg 1998; Munno et al 2000; Dmetrichuk et al 2008; Milanese et al 2009; Nejatbakhsh et al 2011 and others ), (2) growth cone motility and development (Spencer et al 1998; Dmetrichuk et al 2008; Suter 2011), (3) neurite-soma and soma-soma synaptogenesis (Munno et al 2000; Hu et al 2004; Onizuka et al 2012) and (4) neuronal receptors and cell-to-cell neurotransmitter signaling (White and Laczmarek 1997; Mapara et al 2008; Giachello et al 2010; Ye et al 2010). …”
Section: Molluscan Primary Cell Culturesmentioning
confidence: 99%
“…In addition related molecular species have been recently demonstrated in the nervous tissue of the terrestrial snail Helix Pomatia. 83,84 Together, these data support a highly conserved role for these molecules along phylogenesis.…”
Section: The F3/contactin Glycoproteinmentioning
confidence: 53%